The effect of a motivational intervention on weight loss is moderated by level of baseline controlled motivation - Tate Deborah F; Gabriele Jeanne M; Webber Kelly H; Dignan Mark B (BMC, 2010)
Abstract Background Clinic-based behavioral weight loss programs are effective in producing significant weight loss. A one-size-fits-all approach is often taken with these programs. It may be beneficial to tailor programs based on participants' baseline characteristics. Type and level of motivation may be an important factor to consider. Previous research has found that, in general, higher levels of controlled motivation are detrimental to behavior change while higher levels of autonomous motivation improve the likelihood of behavior modification. Methods This study assessed the outcomes of two internet behavioral weight loss interventions and assessed the effect of baseline motivation levels on program success. Eighty females (M (SD) age 48.7 (10.6) years; BMI 32.0 (3.7) kg/m2; 91% Caucasian) were randomized to one of two groups, a standard group or a motivation-enhanced group. Both received a 16-week internet behavioral weight loss program and attended an initial and a four-week group session. Weight and motivation were measured at baseline, four and 16 weeks. Hierarchical regression analysis was conducted to test for moderation. Results There was significant weight loss at 16-weeks in both groups (p < 0.001); however there were no between group differences (p = 0.57) (standard group 3.4 (3.6) kg; motivation-enhanced group 3.9 (3.4) kg). Further analysis was conducted to examine predictors of weight loss. Baseline controlled motivation level was negatively correlated with weight loss in the entire sample (r = -0.30; p = 0.01). Statistical analysis revealed an interaction between study group assignment and baseline level of controlled motivation. Weight loss was not predicted by baseline level of controlled motivation in the motivation-enhanced group, but was significantly predicted by controlled motivation in the standard group. Baseline autonomous motivation did not predict weight change in either group. Conclusions This research found that, in participants with high levels of baseline controlled motivation for weight loss, an intervention designed to enhance motivation for weight loss produced significantly greater weight loss than a standard behavioral weight loss intervention.